Occupational exposure to pesticides are associated with fixed airflow obstruction in middle-age. Issue 11 (7th July 2017) - Alif, Sheikh M; Dharmage, Shyamali C; Benke, Geza; Dennekamp, Martine; Burgess, John A; Perret, Jennifer L; Lodge, Caroline J; Morrison, Stephen; Johns, David Peter; Giles, Graham G; Gurrin, Lyle C; Thomas, Paul S; et al.
Abstract : Rationale: Population-based studies have found evidence of a relationship between occupational exposures and Chronic Obstructive Pulmonary Disease (COPD), but these studies are limited by the use of prebronchodilator spirometry. Establishing this link using postbronchodilator is critical, because occupational exposures are a modifiable risk factor for COPD. Objectives: To investigate the associations between occupational exposures and fixed airflow obstruction using postbronchodilator spirometry. Methods: One thousand three hundred and thirty-five participants were included from 2002 to 2008 follow-up of the Tasmanian Longitudinal Health Study (TAHS). Spirometry was performed and lifetime work history calendars were used to collect occupational history. ALOHA plus Job Exposure Matrix was used to assign occupational exposure, and defined as ever exposed and cumulative exposure unit (EU)-years. Fixed airflow obstruction was defined by postbronchodilator FEV1 /FVC <0.7 and the lower limit of normal (LLN). Multinomial logistic regressions were used to investigate potential associations while controlling for possible confounders. Results: Ever exposure to biological dust (relative risk (RR)=1.58, 95% CI 1.01 to 2.48), pesticides (RR=1.74, 95% CI 1.00 to 3.07) and herbicides (RR=2.09, 95% CI 1.18 to 3.70) were associated with fixed airflow obstruction. Cumulative EU-years to all pesticides (RR=1.11, 95% CI 1.00 to 1.25) and herbicides (RR=1.15, 95% CI 1.00 to 1.32) were also associated with fixed airflow obstruction. In addition, all pesticides exposure was consistently associated with chronic bronchitis and symptoms that are consistent with airflow obstruction. Ever exposure to mineral dust, gases/fumes and vapours, gases, dust or fumes were only associated with fixed airflow obstruction in non-asthmatics only. Conclusions: Pesticides and herbicides exposures were associated with fixed airflow obstruction and chronic bronchitis. Biological dust exposure was also associated with fixed airflow obstruction in non-asthmatics. Minimising occupational exposure to these agents may help to reduce the burden of COPD.